(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the modern society, the usage of computers is increasing day by day and is used in diverse areas. A lot of computer applications exist in almost every area in ever day life, reliability becomes a very extent, since in the matter of economy. Finally for producing software with high reliability, to develop a number of models and to make necessary measuring and its control of functionality. There are several software reliability growth models that can be used to forecast software system reliability.